Black boy : (American hunger), a record of childhood and youth - Wright, Richard, 1908-1960 (HarperPerennial Modern Classics, 2008)
The author grew up in the woods of Mississippi amid poverty, hunger, fear, and hatred. He lied, stole, and raged at those around him; at six he was a "drunkard", hanging about in taverns. Surly, brutal, cold, suspicious, and self-pitying, he was surrounded on one side by whites who were either indifferent to him, pitying, or cruel, and on the other side by blacks who resented anyone trying to rise above the common law. This is the author's powerful account of his journey from innocence to experience in the Jim Crow South. It is an unashamed confession and a profound indictment, a poignant and disturbing record of social injustice and human suffering.